2018
DOI: 10.1080/24748668.2018.1509254
|View full text |Cite
|
Sign up to set email alerts
|

Chinese soccer association super league, 2012–2017: key performance indicators in balance games

Abstract: The aim of the present study was to identify the game-related statistics which discriminate between winning, drawing and losing teams in Chinese Soccer Association Super League. The sample included 1056 balance games from the 2012-2017 Chinese Soccer Association Super League. Physical and technical game-related statistics were gathered. A one-way analysis of variance and discriminant analysis of data was done. The results showed that winning teams were significantly higher for the following game statistics: sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 29 publications
(38 reference statements)
3
32
0
1
Order By: Relevance
“…Variables utilised in this study were identified by previous literature (Hughes et al, 2012;Jamil, McErlain-Naylor, et al, 2020;Lago-Peñas et al, 2010;Liu et al, 2016;Zhou et al, 2018) and therefore consisted of a total of 43 technical metrics. These variables were categorised into four areas, shooting, passing, defensive | 2020 | ISSUE -| VOLUME --© 2020 University of Alicante and errors.…”
Section: Data and Variablesmentioning
confidence: 99%
See 3 more Smart Citations
“…Variables utilised in this study were identified by previous literature (Hughes et al, 2012;Jamil, McErlain-Naylor, et al, 2020;Lago-Peñas et al, 2010;Liu et al, 2016;Zhou et al, 2018) and therefore consisted of a total of 43 technical metrics. These variables were categorised into four areas, shooting, passing, defensive | 2020 | ISSUE -| VOLUME --© 2020 University of Alicante and errors.…”
Section: Data and Variablesmentioning
confidence: 99%
“…Recent years have seen much research focussed on factors that impact player performance in football with some research focussing upon the physical aspects of player performance (Andrzejewski et al, 2013;Di Salvo et al, 2009), technical aspects of player performance (Fernandez-Navarro et al, 2016;Jamil, McErlain-Naylor, et al, 2020;Liu et al, 2013), or both physical and technical parameters (Bush et al, 2015;Zhou et al, 2018). It has been widely acknowledged that performance in football is influenced by a combination of physiological, psychological, tactical and technical variables (Hughes et al, 2012) demonstrating the multifaceted nature of performances in football where many parameters contribute to success (Mackenzie & Cushion, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, in open sports such as soccer, which takes place in a dynamic context with a multitude of interactions and possibilities, the factors that modulate an athlete's performance are even more complex. Those that have been described include physical, technical, and tactical demands, field positioning, and players' roles, among others [3][4][5]. Although some authors have focused on individual actions to explain sports performance [6], there are numerous studies that have attempted to analyze the interactions between different variables and how these influence group factors, such as training and the tactical component, among others, to explain performance from a group dimension [7][8][9].…”
Section: Introductionmentioning
confidence: 99%